Cigarette Use Among American Indians and Alaska Natives in Metropolitan Areas, Rural Areas, and Tribal Lands. (September 2019) - Cunningham, James K.; Ritchey, Jamie; Solomon, Teshia A.; Cordova, Felina M.
Abstract : Context: Cigarette use among the US general population is significantly lower in metropolitan areas than in rural areas. Objective: To assess whether cigarette use among American Indians and Alaska Natives (AI/AN) is lower in metropolitan areas than in rural areas and tribal lands (which are predominantly rural). Design: Data came from the National Survey on Drug Use and Health (2012-2016). Regressions with adjustments for demographics were performed to assess whether cigarette use differed in association with type of place. Settings: The AI/AN in tribal lands (n = 1569), nontribal large metropolitan (1+ million people) areas (n = 582), nontribal small metropolitan (<1 million) areas (n = 1035), and nontribal rural areas (n = 1043). Main Outcome Measures: Cigarette abstinence, current smoking, daily use, number of cigarettes used, and days of use—all in the past month. Nicotine dependence was also examined. Results: Metropolitan (large or small) areas versus rural areas: no statistically significant differences in cigarette use were found. Metropolitan (large or small) areas versus tribal lands: days of cigarette use and daily use were significantly lower in tribal lands. Tribal lands were also lower than small metropolitan areas regarding number of cigarettes used and nicotine dependence. Rural areas versus tribal lands: cigarette measures were consistently lower in tribal lands. For example, the prevalence of current smokers, daily users and nicotine dependence, respectively, was 37.9%, 25.9%, and 16.3% in rural areas and 27.4%, 13.6%, and 8.9% in tribal lands. Conclusions: Differences in cigarette use between AI/AN in nontribal rural and metropolitan areas were not indicated. Instead, the place differences found were lower cigarette use in tribal lands than in nontribal rural areas and, to some extent, metropolitan areas. These findings can help inform policy makers working to develop context-sensitive anticommercial tobacco efforts for AI/AN.